Sequential Changes in Progression of Ossification in Middle Ear Ossicles of Nellore Sheep Fetus - V., Karunasri (Indian Journal of Veterinary Anatomy, 2018)
Nellore Sheep fetuses aged between 58 to 145 days were studied to elucidate the ossification pattern of middle ear ossicles. Fetal heads were subjected to Alizarin red- S staining and the middle ear ossicles were also dissected out. In malleus, incus and stapes the ossification started at 63, 78 and 80 days respectively in sheep fetuses. The ossification initiated in the head of malleus extended towards lamina, neck, muscular process, lateral process and handle of the malleus. The body of incus was ossified first then extended towards the short limb and long limb. Ossification started in the region of foot plate facing obturator foramen and extended towards the base, crura and finally the head of stapes. Ossified area of malleus at 145 days was 68.58%, in incus 83.82% and in stapes 67.45%.The study was also supported by computed radiography. It could be concluded that ossification of middle ear ossicles continued postnatally also in sheep.